Strontium nitrate-dopped zinc oxide-loaded alginate gels with gentamicin for improved wound healing - Suhair Hikmat; Ola Tarawneh; Lama Hamadneh; Rania Hamed; Ala A. Alhusban; Mohammad Hailat; Hadeel Abu Mahfouz; Sawsan Shraim; Alghadeer Al-Shammari; Aya Aljariri; Rafa Abu Rayya; Lana Hamdan (Journal of Materials Science: Materials in Medicine)
Abstract Wound dressing development is an area of active research. Traditional dressings lack antibacterial activity, biocompatibility, and tissue regeneration. Alginate is a heavily investigated polymer employed as wound dressings and can be combined with a wide range of additives. Herein, we report the preparation of alginate gel using the crosslinking technique as potential wound dressing, with insight investigation of the influence of employing single, two, or three cross-linkers: Strontium (Sr), zinc oxide (ZnO), and gentamicin sulfate. Rheology was used to confirm the gel’s preparation, where the samples’ viscosity curves show decreased viscosity with increased shear rate, indicating pseudoplastic flow. The linear viscoelastic region shows constant G’ and G” within the sample structure. In this study, we used three gels with different mixtures of ingredients: Gels A, B, and C contain sodium alginate (1% w/v) and 0.5 mL of Sr nitrate (4% w/v). However, Gels B and C contain 0.25 mL of ZnO (0.5% w/v). Gel C also includes 0.1 mL of gentamicin (1% w/v). The study examined the effectiveness of Gel A, B, and C on wound healing, calculating the reduction of wound area after seven, 14, and 20 days of a single topical treatment. Gel A, B, and C significantly reduced wound area, while Gel B and C showed a significant reduction. The zone of inhibition was used to detect the gels’ efficacy against microorganisms. The study found zinc deposition in the liver and bone, with Gel B and C showing higher levels. The study also found significant overexpression of MIP α and MIP β in tissues and downregulation of CCL2, IL8, and TGF β, explaining wound healing with minimal scar formation. Graphical Abstract